Coupling environmental modeling with GIS as a tool for assessing water quality in Nhue Watershed, Vietnam - Le Phu, Tuan; Ballesteros, Florencio C. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
One of the urgent issues in water resources management in the Nhue river basin is water quality deterioration resulting from industrial, agricultural and domestic discharges. This study evaluated water quality in Nhue watershed by using the Soil and Water Assessment Tool (SWAT) model. Data required for this study were compiled from different sources, including Digital Elevation Model (DEM) data taken from Shuttle Radar Topographic Mission (SRTM), land use data from Global Land Cover Facility among others. The data for calibration and validation were collected from Vietnam Environmental Protection Agency. Four water quality parameters from the simulation in SWAT were assessed, including NH4+, NO2-, NO3- and PO43-. Comparing the above parameters with National Technical Standards for surface water quality (QCVN08:2008/MONRE), showed that water quality of Nhue watershed through Hanoi Capital were contaminated thus downgrading its best usage to transportation purposes or other purposes requiring low water quality. This study was able to demonstrate marked utility of SWAT and GIS in water quality modeling and by extension, to management planning activities in a given watershed.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Water quality biological assessment; Water quality -- Vietnam